2010
DOI: 10.1590/s1516-80342010000100024
|View full text |Cite
|
Sign up to set email alerts
|

Alterações no sistema vestibulococlear decorrentes da exposição ao agrotóxico: revisão de literatura

Abstract: Os agrotóxicos são amplamente utilizados no meio rural e sua larga utilização, desprovida de medidas de biossegurança apropriadas, vem provocando impactos potenciais tanto para a degradação ambiental quanto para o organismo humano, aumentando a incidência de intoxicações ocupacionais. O objetivo do presente estudo foi revisar e discutir a respeito da exposição aos agrotóxicos e sua influência na função e estrutura do sistema auditivo. Foram revisados periódicos nacionais e internacionais relevantes indexados n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(31 reference statements)
0
6
1
4
Order By: Relevance
“…The reason may be the hearing health mantainence depends on set of factors as the quantity and the frequency of pesticides exposition, the concurrent operating noise equipment, and the lack of individual protection 4,8,[23][24][25] ; in the current research, most subjects operated noise equipment at work, handled pesticides, and used individual protection device (Table 3). These findings are different from other studies 5,10 of the same theme, because most farmers reported not using the protection device for several reasons, as: financial issues to acquire the individual protection device, troubles using it due to warmth, discomfort and lack of habit to use it 10,23 .…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The reason may be the hearing health mantainence depends on set of factors as the quantity and the frequency of pesticides exposition, the concurrent operating noise equipment, and the lack of individual protection 4,8,[23][24][25] ; in the current research, most subjects operated noise equipment at work, handled pesticides, and used individual protection device (Table 3). These findings are different from other studies 5,10 of the same theme, because most farmers reported not using the protection device for several reasons, as: financial issues to acquire the individual protection device, troubles using it due to warmth, discomfort and lack of habit to use it 10,23 .…”
Section: Discussioncontrasting
confidence: 92%
“…Farmers are part of the group of works exposed to noise and defensive farming products 4 that, due to lack of information and guidance about the risk of the defensive products to health, may overestimate the benefic effects of these products in plantation and disregard the detriments to health in short, medium and long term 5,6 . Among the several factors making farmers susceptible to the harmful effects caused by pesticides, the highlight goes to the hard access to information and education by the products' users, as the low control about its production, distribution, and use 2,7 .…”
Section: Introductionmentioning
confidence: 99%
“…O seu potencial no controle de pragas agrícolas, foi comprovado em vários estudos (REDOAN et al 2010, BRUSTOLIN et al 2011, GUEDES et al 2012, VIEIRA et al 2012. Foi igualmente demonstrada a relação entre a exposição aos pesticidas e a ocorrência de doenças como a Leucemia em crianças (TURNER et al 2011, FERREIRA et al 2012), a doença de Parkinson (PEREIRA & GARRETT 2010, BARTH & BIAZON 2010, as lesões no sistema auditivo (KORBES et al 2010, KÓS et al 2013, efeitos deletérios sobre parâmetros seminais (CASTRO et al 2014, MINGUEZ-ALÁRCON 2014 e ao fraco desenvolvimento cognitivo e/ou neuropatia (SOUZA et al 2011, CAMPOS et al 2015.…”
Section: Introductionunclassified
“…However, studies on the toxic effects of pesticides on the auditory system are still scarce. For example, it is known that rodents exposed to pesticides present morphological alterations to their cochlea in the three spirals analyzed, in the cells of the saccule and utricle (10) . Some studies carried out with evoked otoacoustic emissions (EOAE) in individuals exposed to noise found a reduction in the level of responses at the frequencies studied (11,12) .…”
Section: Introductionmentioning
confidence: 99%